Capacity Building of Dage Craftsmen Group Ciberung Village Through Organizational Governance Training - Famila Dwi Winati; Irwan Susanto; Aiza Yudha Pratama; Nurul Latifasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Ciberung Village is one of the villages in Ajibarang Sub-district, Banyumas Regency, Central Java, known as the center of dage production and business. The typical dage of Ciberung Village is made from copra pulp or cake. Currently, the production and marketing of dage as a village potential is still managed individually by each craftsman. Thus, dage products on the market often need to be standardized in terms of taste, quality, texture, and price. These standardization efforts then impact the uneven economic benefits felt by dage craftsmen. Therefore, this community service activity aims to increase the community's competitive advantage through mentoring and reactivating dage craftsmen groups through institutional and organizational governance training. This program consists of four main stages: analysis of partner conditions, focus group discussions, socialization and training, and evaluation. Through this activity, the understanding of the community and village government regarding the management of dage business and production in an integrated manner through groups and its benefits can increase. The program evaluation results showed that 93% of the craftsmen agreed to create a Dage Craftsmen Group. In addition, there was an increase in understanding of the organization in general to understanding the benefits of establishing dage craftsmen in terms of economic, marketing, and social aspects with an average of 92.5%.